PENGARUH TINGKAT SUKU BUNGA (BIRATE) DAN KURS DOLAR AS TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DENGAN MENGGUNAKAN METODE ERROR CORECTION MODEL (ECM) - Muhammad Mahdi; David Kaluge (Jurnal Ekonomi Pembangunan, 2010)
This research to determine whether, exchange rate, interest rate (BI Rate) have an influence on Indeks Harga Saham Gabungan (IHSG). The data used are secondary data from the period June 2008 to August 2010. The analytical tool used in this research is the error correction model (ECM). Previously conducted tests stasioneritas namely the root of the test unit and test the degree of integration and cointegration tests. Based on the test stasioneritas obtain stationary data on a Zero level at a significance level of 10% and other data on the first level and terkointegrasi diffirence on the zero level at 1% level of significance. The result of an error correction model analysis showed that in short term interest rate (BI Rate), Ezchange rate, significantly influences the IHSG fluctuates, while the long-term variable Exchange rate has a significant while variable interest rate is not significant.